2018
DOI: 10.29245/2578-3009/2018/si.1106
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Epidemic Meningitis in the African Region: Progress and Challenges:2010-2016

Abstract: Background Epidemics of meningococcal disease constitute a major public health challenge in Africa, affecting mostly the 24 countries of the meningitis belt. These epidemics led to a call for a call for a safe, effective and affordable conjugate vaccine against the major serogroup responsible for recent epidemics by leaders of the region. Objective This paper documents experiences with efforts at eliminating epidemic meningitis in the African Region. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The study found the decline of N. meningitidis A after 2010 with the introduction of MACV and the predominance of other meningitis pathogens (N. meningitidis W135, N. meningitidis C, N. meningitidis X, and Streptococcus pneumoniae) with the near disappearance of N. meningitidis A cases and epidemics in African meningitis belt countries [18,21,[24][25][26][27][28]. The results of the study confirmed those found in the literature.…”
Section: Bacterial Meningitis Pathogens After Macv Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The study found the decline of N. meningitidis A after 2010 with the introduction of MACV and the predominance of other meningitis pathogens (N. meningitidis W135, N. meningitidis C, N. meningitidis X, and Streptococcus pneumoniae) with the near disappearance of N. meningitidis A cases and epidemics in African meningitis belt countries [18,21,[24][25][26][27][28]. The results of the study confirmed those found in the literature.…”
Section: Bacterial Meningitis Pathogens After Macv Introductionsupporting
confidence: 82%
“…The reduction of the incidence of bacterial meningitis cases, epidemics and deaths following the introduction of MACV into meningtis belt was demonstrated [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Novak et al showed 71% decline in risk of meningitis (suspected cases) in Burkina Faso 1 year after the introduction of MACV [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No cases of Neisseria meningitidis serogroup A have been identified in the vaccinated population [21, 24]. Such concerted efforts showcase the pivotal role that understanding the aetiology of CNS infections can play in preventing future neurological infectious outbreaks [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to assess the landscape of CNS pathogens affecting the West African region beyond our initial synthesis. Having already translated research on neurological infections into successful policy in this region in the cases of meningitis and also poliomyelitis, a model for future action exists [26]. Many other pathogenic causes of CNS infections pose significant risks for outbreaks and necessitate increased attention [21].…”
Section: Discussionmentioning
confidence: 99%